Hippocampal region metabolites and cognitive impairment in patients with general paresis: based on 1H-proton magnetic resonance spectroscopy - Che, Xin; Miao, Tianyang; Shi, Haishan; Li, Zezhi; Ning, Yuping (Frontiers in Pharmacology, 2024)
Background: This study utilizes Hydrogen proton magnetic resonance spectroscopy( 1 H-MRS) to investigate metabolite concentrations in the bilateral hippocampus of general paresis (GP) patients. Methods: A total of 80 GP patients and 57 normal controls (NCs) were enrolled.Metabolite ratios in the bilateral hippocampus were measured using 1H-MRS.Based on MMSE scores, participants were categorized into normal control, mild cognitive impairment, and moderate-severe dementia groups. Metabolite ratios (Nacetylaspartate (NAA)/creatine (Cr), choline (Cho)/ creatine (Cr), N-acetylaspartate (NAA)/ choline (Cho), myoinositol (MI)/ creatine (Cr), choline (Cho)/Nacetylaspartate (NAA)) were compared between groups, and correlations between metabolite ratios and cognitive performance were examined. Results: MMSE scores progressively decreased in the normal, mild cognitive impairment, and moderate-severe dementia groups (p<0.001). The moderate-severe dementia group showed significantly lower NAA/Cr ratios in the left hippocampus region (L-NAA/Cr ratios) (p<0.001) and higher Cho/NAA ratios in the left hippocampus region (L-Cho/NAA ratios) (p<0.05) compared to the other groups. However, differences in L-NAA/Cr and L-Cho/NAA ratios between the mild cognitive impairment group and the NC group were not significant in the 4 hippocampus region (p>0.05). NAA/Cho and NAA/Cr ratios in the right hippocampus region (R-NAA/Cho and R-NAA/Cr ratios) in the moderate-severe dementia group were lower than those in the control group (p<0.05). No correlation was found between metabolite ratios and MMSE scores in bilateral hippocampus regions. Conclusion: There are distinctive metabolic characteristics in the hippocampus of GP patients. GP patients exhibited lower NAA/Cr and NAA/Cho ratios in the bilateral hippocampus, indicating neuron loss in these areas, which may become more pronounced as the disease progresses.